Peranan Bapa Dalam Pembentukan Keluarga Sejahtera: Analisa Isu-Isu Dan Cabaran Di Era Digital: The Role of Fathers in the Formation of Well-Being Family: An Analysis of Issues and Challenges in the Digital Era - Hasri Harun; Hasliza Mohamad Ali (Online Journal of Research in Islamic Studies, 2021)
The well-being family which is formed based on the Qur’an and Sunnah results from the role- played by fathers as the head of the family. Previous studies have proven that the role of a quality father produced children who are excellent and balanced from the physical, emotional, spiritual, intellectual, and social aspects. However, there are also challenges and tribulations in the formation of the family caused by neglecting the role of fathers who is the head of the household, especially in the digital era. This article aimed to analyze the issues and challenges of the role of fathers in the development of well-being families in the digital era. Moreover, this article used a qualitative method by evaluating the role of fathers based on the literature reviews and observations from primary and secondary sources. The findings of this study provided an impact not only input but also useful guidance to father and also included economic, social, and religious aspects. Therefore, efforts to empower the role of fathers should not be sidelined and should be given fair attention. Accordingly, it needs to be documented and practiced as a guide to fathers to build the well-being family in this challenging digital era.